Women’s experiences of accessing individualized disability supports: gender inequality and Australia’s National Disability Insurance Scheme - Sophie Yates (BMC, 2021)
Abstract Background Care services in industrialized nations are increasingly moving towards individualized funding models, which aim to increase individuals’ flexibility, choice and control over their services and supports. Recent research suggests that such schemes have the potential to exacerbate inequalities, however none has explored gendered dimensions of inequality. The Australian National Disability Insurance Scheme (NDIS) is a major individualized funding reform, and has a female participation rate of only 37%, despite women and girls making up half of the disability population. Methods The objective of the study is to explore possible gendered barriers to applying for and receiving adequate support through the NDIS, and to suggest directions for future research. We report on semi-structured interviews with 30 women with disability and explore their experiences with the NDIS and their perspectives on challenges associated with being a woman seeking disability support in Australia. We analyse the results using thematic analysis. Results Most women in our sample reported differences between the experiences of men and women seeking disability support in Australia. Commonly reported gendered barriers to women being able to access the right supports for their disability involve a) confidence, negotiation and self-advocacy, b) gendered discrimination in diagnosis and the medical system, which has implications for disability support access, and c) support for and recognition of caring roles. Conclusions These results suggest that women are not receiving equitable treatment with regard to the NDIS, and that further research and policy reform are needed to ensure that women with disability are not further disadvantaged as a result of the move toward individualized funding models.